BERMAIN PERAN MODEL PEMBELAJARAN KOMUNIKATIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA KOMPETENSI PEMAPARAN JATI DIRI DI KELAS X ADMINISTRASI PERKANTORAN 1 SMK NEGERI 2 PURWOREJO SEMESTER GASAL TAHUN PELAJARAN 2015 – 2016 - Abas Romadi (p-ISSN 2356-0576, 2018)
Abstract: This Research has the background of the fact that the ability of class X Administration Office 1 SMK Negeri 2 Purworejo to speak English on the competence of introduction is still low. The problems studied are (1) how is the implementation of role playing model to increase learning motivation and learning outcomes of speaking for students in competenceof  introduction, (2) how to increase motivation to learn English for students by using role playing model, and (3) how to increase the results of students learning to speak English on the competence of  introduction using role playing model. The objectives research are (1) to investigate the implementation of role playing model in improving learning motivation and learning outcomes of speaking for students in the competence ofintroduction, (2) to determine and increase students' motivation by using role playing model, and (3) to know and improve the results of students learning to speak English on the competence of  introduction using role playing model. This research is carried out in class X Administration Office 1 SMK Negeri 2 Purworejo in the academic year 2015/2016. Subject research is consisted of 32 students. This research is conducted for 2 months in two cycles. Instruments research used are speaking assessment sheets, questionnaires and observation sheets. The data are analyzed descriptively by using percentage analysis. After the implementation of the action research, it is found that role playing model is able to improve the competence of speaking for students. This conclusion is derived from data analysis, the average number of students from pre-acquisition research at 62.81 and the average number of students in the first cycle to 70.78 and the second cycle increase to 75.85. In addition, there are changes of attitude of students in speaking on the competence of introduction from negative to positive.   Keyword: Role Playing, Communicative Language Teaching (CLT), Speaking Skills